Euro Area banks' sensitivity to changes in carbon price - Marco Belloni; Friderike Kuik; Luca Mingarelli (European Central Bank (ECB), 2022)
In recent years there has been growing attention on the risks posed by climate change. One relevant question for financial stability is to which extent the materialisation of transition risks emerging from the sudden implementation of climate change mitigation policies would impact the financial system. In this paper we analyze the effects of changes in carbon price on the European banking system. We assess this climate change transition risk through a banking sector contagion model where firms are negatively impacted by an increase in carbon prices. Using a unique granular dataset we evaluate the consequences of a combination of different increases in carbon prices and firm emission reduction strategies. We find that taking early policy action, implying more gradual changes in carbon prices, is not expected to lead to adverse impacts on the banking system, especially if firms reduce their emissions efficiently. Conversely, a disorderly, abrupt transition to a low carbon economy requiring very high sudden changes in carbon prices might have disruptive effects on the financial system, especially if firms fail to reduce their emissions.
Keywords: Q48; Q54; Q58; 330; Empirical Banking; Financial Networks; Climate Change; Transition Risk